Integrating Maqasid Syariah into Sustainable Halal Tourism in Southeast Asia: A Systematic Literature Review - Fiya Ainur Rohmatika; Zainur Ridho; Moch Malik Dzulpikar; Joko Sutopo; Zidna Alaal Mujtaba; Andhika Nur Kurniawan (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to develop an integrative conceptual framework linking Sharia objectives (maqasid al-sharia) with sustainable halal tourism in Southeast Asia through research landscape mapping, identification of key findings, and a comprehensive literature synthesis. Method: This study employs a mixed-methods approach integrating bibliometric analysis with a systematic literature review based on the PRISMA 2020 protocol. A total of 62 Scopus-indexed articles from 2019 to 2025 were analyzed using VOSviewer software to identify major thematic clusters. Result: The bibliometric analysis revealed five main thematic clusters: halal tourism and Islamic marketing; tourist satisfaction and loyalty; sustainable tourism; Muslim tourists and destination development; and religiosity and local wisdom. The findings indicate that maqasid al-sharia serves as an integrative axis capable of bridging fragmentation among these clusters. The dynamics of implementing sustainable halal tourism in Malaysia, Brunei Darussalam, and Indonesia reveal diverse approaches grounded in maqasid al-sharia principles. Contribution: This study demonstrates that maqasid al-sharia can serve as a normative foundation for developing halal tourism that is ecologically, socially, and economically sustainable. The resulting integrative conceptual framework offers practical implications for policymakers, destination managers, and industry stakeholders in building a tourism ecosystem that is not only Sharia-compliant but also resilient, while contributing new theoretical knowledge by bridging the gap between Sharia principles and the global sustainability agenda.